Prevalence and Risk Factors Associated With Postpartum Depressive Symptoms Among Women in Vientiane Capital, Lao PDR - Xayyabouapha, Amkha; Sychareun, Vanphanom; Quyen, Bui Thi Tu; Thikeo, Manivone; Durham, Jo (Frontiers in Public Health, 2022)
Postpartum depression (PPD), the onset of depressive episodes after childbirth, is the most common psychological condition following childbirth, and a global public health concern. If undiagnosed and/or untreated, postpartum depression can have negative effects on maternal and child health, however, there are few studies on the prevalence of postpartum depression in low- and middle-income countries. To contribute to filling this gap, this study examined the prevalence and risk factors associated with postpartum depressive symptoms among women after delivery in Vientiane Capital, Lao PDR. The study was a cross-sectional design, with multistage sampling used to identify women between 4 and 24 weeks after giving birth (N = 521). The Edinburgh Postnatal Depression Scale was used to identify women with postpartum depressive symptoms. Univariate and multivariate logistic regressions identified risk factors associated with postpartum depressive symptoms. The prevalence of postpartum depressive symptoms among participants was 21.3%. Associated factors were having at least 2–3 living children (AOR: 1.9, 95% CI: 1.1–3.0), experiencing mental health problems during pregnancy (AOR: 3.3, 95% CI: 1.4–7.6), experiencing conflicts with family members (AOR: 2.5, 95% CI: 1.5–4.0), the experience of intimate partner violence (AOR: 2.6, 95% CI: 1.3–5.5), and receiving moderate social support (AOR: 5.6, 95% CI: 3.2–10.0). In contexts where access to mental health specialists has severely constrained maternal and child healthcare providers at primary health care must be supported to develop the necessary skills to identify risk factors and symptoms and offer basic essential services for postpartum depressive symptom (PDS). The study identified a high proportion of mothers with postnatal depressive symptoms, highlighting the need to screen and treat mothers who present with PDS, as not doing so exposes mother and their children to a range of negative health and social outcomes. Addressing the stigma associated with mental health illness and mental health illness and domestic violence that prevents women from seeking healthcare, must also be developed, implemented, and evaluated.